Supervising counselors and therapists : a developmental approach - Stoltenberg, Cal D.; Delworth, Ursula (San Francisco, Calif. : Jossey-Bass, 1987)
Presents a comprehensive approach to clinical supervision through which entry-level counselors become seasoned professionals. It explains the needs and characteristics of trainees and recommends how and when supervisors may intervene to help trainees handle counseling sessions with clients.
Bibliography: p. 197-212.
Keywords: Counselors -- Supervision of; Psychotherapists -- Supervision of; Counseling